A Proposal for an Effective Privacy-Preserving Query Solution for Mobile Devices - Ingole, Kartik (Journal of Electronic Design Engineering, 2023)
The prevalence of smartphones has led to increased recognition and significance of location-based services (LBS). Irrespective of the use of Location-Based Services (LBS), it also raises a significant concern about the security of the user’s location. This research presents a novel approach for enhancing security in geographic range queries via the development of a secured traveller application. The objective is to transfer the local area-based administration (LBS) information from the LBS provider to the cloud and subsequently from the cloud to the LBS client without compromising security. To provide secure spatial range queries, we offer a main predicate encryption scheme for internal item retrieval. This scheme may be used to determine whether a location falls inside a specified circular area in a privacy-preserving manner. To refrain from scrutinizing all points of interest (POIs) to identify coordinated POIs, we also use a unique file structure known as the ss tree. This structure effectively conceals sensitive location information using our IPRE scheme. In the context of a portable location-based services (LBS) client operating on an Android smartphone, it is anticipated that the generation of a query will take around 0.9 seconds.